Cost-effectiveness of vaccination against cytomegalovirus (CMV) in adolescent girls to prevent infections in pregnant women living in France. Issue 10 (28th February 2018) - N'Diaye, D.S.; Launay, O.; Picone, O.; Tsatsaris, V.; Azria, E.; Rozenberg, F.; Schwarzinger, M.; Yazdanpanah, Y.
Abstract: Background: CMV infections are the most frequent congenital infections worldwide. Aim: Assess the cost-effectiveness of vaccination strategies of adolescent girls vs. current practice (hygiene counseling) to prevent CMV seroconversions during pregnancy in France. Method: A Markov decision-tree model simulated overtime the trajectory of a single fictive cohort of 390, 000 adolescent women aged 14 years old, living in France. Impact of vaccination was explored until the end of their reproductive live 40 years later. Strategies compared: "S1: No vaccination" (current practice); "S2: Routine vaccination"; "S3: Screening and vaccination of the seronegative". Model parameters: Seroconversion rate without vaccination (0.035%/pregnant woman-week); fetal transmission risk (41%). Vaccine vs. no vaccination: a 50% decrease in maternal seroconversions. Outcomes: Quality-Adjusted Life-Years (QALYs) of the cohort-born babies; discounted costs; Incremental Cost-Effectiveness Ratio (ICER). Results: S2 was the most effective strategy (with 35, 000 QALYs gained) and the most expensive (€211, 533, 000); S1 was the least effective and least costly (€75, 423, 000). ICERs of strategy S3 vs. S1, and S2 vs. S3 were 6, 000€/QALY gained (95% uncertainty range [2700–13, 300]) and 16, 000€/QALY [negative ICER (S3 dominated by S2) – 94, 000] gained, respectively; highly cost-effective because ICER < 1∗France's GPD/capita = €30, 000. Sensitivity analysis: If the seroprevalence was >62% (vs. 20% in the base case), S3 would become the most efficient strategy. Conclusion: In France, systematic vaccination of adolescent girls was the most efficient strategy to prevent maternal seroconversions. If the population was less than 62% immune, systematic screening and vaccination of susceptibles would become the most cost-effective approach.